2017
DOI: 10.1111/bjd.15495
|View full text |Cite
|
Sign up to set email alerts
|

Light therapies for acne: abridged Cochrane systematic review including GRADE assessments

Abstract: Summary We undertook a Cochrane review of randomized controlled trials (RCTs) evaluating the effects of light‐based interventions for acne vulgaris. We searched the Cochrane Skin Specialised Register, CENTRAL, MEDLINE, Embase, LILACS, ISI Web of Science and grey literature sources (September 2015). We used the Grading of Recommendations Assessment, Development and Evaluation Working Group approach to assess the quality of evidence (QoE). We included 71 RCTs (4211 participants, median sample size 31). Results f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Long-term improvements up to 1 year have been documented with laser treatments and they need to be explored further in menopausal acne, which is predominantly inflammatory, as they cause minimal side effects 70. However, a recent Cochrane review on light therapies for acne concluded that there is a need for larger studies of better quality to provide evidence of the utility and long-term benefits in acne, particularly considering the cost of laser therapies 71…”
Section: Methodsmentioning
confidence: 99%
“…Long-term improvements up to 1 year have been documented with laser treatments and they need to be explored further in menopausal acne, which is predominantly inflammatory, as they cause minimal side effects 70. However, a recent Cochrane review on light therapies for acne concluded that there is a need for larger studies of better quality to provide evidence of the utility and long-term benefits in acne, particularly considering the cost of laser therapies 71…”
Section: Methodsmentioning
confidence: 99%
“…A review of randomized, controlled studies of light-based therapies for acne treatment concluded that none of the studies demonstrated efficacy; it is necessary to carry out well-designed studies that employ standardized outcome measures as well as comparison with usual drug treatments. 114…”
Section: Systemic Treatmentmentioning
confidence: 99%
“…Although well-designed studies evaluating the effectiveness of non-pharmacological interventions are lacking, circumstantial evidence suggests that the e cacy of these types of therapy are promising. (11)(12)(13) In addition, Waldman et al (2017) reported an expert consensus on the safety of non-pharmacological treatment modalities in the setting of isotretinoin use.…”
Section: Discussionmentioning
confidence: 99%